Benjamin Mancha/Tom Bielorrusso - Carvalho Júnior, Marcelo Barros de (Revista do Colóquio, 2023)
A reflection on colors, sounds and their distortions in the author’s personal and artistic creation universe, which has been unfolding since 2012, on purpose or not. The journey is triggered by listening to the album “Ratos”, created in 2022, but goes through references present both in the album and in other works produced in the last decade, such as musical records, comics and audiovisual productions. An effort was also made to contextualize the production force with mental health themes, more specifically those associated with Bipolar Affective Disorder.